Efficiency of fungicides in the treatment of maize seeds to control Fusarium moniliforme and Pythium sp. - Pinto, Nicésio Filadelfo Janssen de Almeida (Pesquisa Agropecuaria Brasileira, 1997)
The efficiency of the fungicides Captan, Thiran, Thiabendazole, Quintozene and Etridiazole + Quintozene in the treatment of BR 106 maize seeds to control Fuzarium moniliforme and Pythium sp. was studied. Seed health, seedling emergence in sterilized soil, germination, vigor, field emergence, and emergence in the cold tests in a maize monoculture and in a soil infected with Pythium sp. or with Fusarium moniliforme were evaluated. Captan and Thiram promoted higher control of Fusarium moniliforme in the seed, higher seed viability, and more emergence in cold tests in a soil with monoculture or infected with Pythium sp. In a soil infected with Fusarium moniliforme, Thiabendazole and Captan were the most efficient. No benefit was shown by the fungicide treatment for germination nor for emergence in field or in sterilized soil. It was concluded that Captan and Thiram were efficient to control Fusarium moniliforme; Thiabendazole and Etridiazole + Quintozene were efficient to control Fusarium moniliforme and Pythium sp.